MARPOL consolidated edition 2017 articles, protocols, annexes and unified interpretations of the International Convention for the Prevention of Pollution from Ships, 1973, as modified by the 1978 and 1997 protocols, incorporating all amendments in force on 1 January 2017. (IMO publication, 2017)
"MARPOL Convention is concerned with preserving the marine environment through the prevention of pollution by oil and other harmful substances and the minimization of accidental discharge of such substances. The 2017 consolidated edition aims to provide an easy and comprehensive reference to the up-to-date provisions and Unified Interpretations of the Articles, Protocols and Annexes of the MARPOL Convention, including the incorporation of all the amendments that have been adopted by the Marine Environment Protection Committee (MEPC)." --Back cover.